Exploring the Factors That Influence College Students' Academic Self-Efficacy in Blended Learning: A Study From the Personal, Interpersonal, and Environmental Perspectives. (June 2022) - Wei, Yitong; Shi, Yinghui; MacLeod, Jason; Yang, Harrison Hao
Academic self-efficacy is identified as one of the strongest predictors of students' academic performance. However, few studies have explored the factors that influence students' academic self-efficacy in a blended learning environment. By developing a comprehensive model, this study investigates the main factors that influence students' academic self-efficacy in blended learning from the personal, interpersonal, and environmental perspectives. The relevant information was acquired through a questionnaire survey. The participants included 366 college students at a university in central China. Hierarchical regression analysis shows that intrinsic motivation, extrinsic motivation, instructor support, performance expectancy, and facilitating conditions are significant predictors of students' academic self-efficacy in blended learning. The findings expand the understanding of students' academic self-efficacy in technology-enhanced learning environments and provide valuable insights that could help to improve the appropriateness of instructional design in blended learning courses.